Household Plant Monitoring System - Suugen Raj, Venugopal (2023)
Almost everyone today has plants in their houses. These plants, also known as household plants, need to be watered everyday as water is an essential part of their growth. Household Plant Monitoring System (HPMS) can gather data of soil moisture, temperature and humidity and display on the web application. At the same time, the data gets stored in the database. The system operates automatically for the irrigation process. User will be sent notifications via email about the irrigation status. Problems leading to the development of this project were lack of plant monitoring by users, most of the agriculture systems that have been developed can only monitor and collect data for one type of plant and lastly, watering the plants manually is not systematic as excess water might be supplied. The aim of this project is to develop a Household Plant Monitoring System (HPMS) for 3 different plants. Several objectives have been identified to achieve the aim. Firstly, design a HPMS to monitor and self-water the plant. Secondly, develop the HPMS integrated with web application to monitor the plants. Thirdly, validate the HPMS that has been developed by using the correct rate accuracy method based on the suitable data for each plant. There are four scopes that have been identified for this project. Plant types used are watermelon, chili and tomato. Technology used are ESP32, soil moisture sensor, DHT11 sensor (temperature & humidity), relay module, water pump, step-down voltage converter and jumper wires. Users are home gardening users and the suitable data consists of soil moisture, temperature, humidity and soil type. Suitable SDLC model chosen for this project is incremental model. Component connection was done in the first increment, following by database set up in the second increment and web application development in the third increment. After completing the project, HPMS system was tested for five days. The system successfully retrieved and stored data into database, displayed sensor readings on the webpage and irrigated automatically according to the conditions set. The readings gathered for each plant were then used to calculate the efficiency of the system using the correct rate formula. In conclusion, all three objectives have been achieved as the HPMS was successfully designed, developed and validated.